Common Words (Odagai) in the Kazakh and Karakalpak Languages, the History of Their Study - Sharipova Zhanar Ganibaevna (Academia One, 2023)
The words belonging to the common word class are a group of words that express different moods of a person, as well as gestures that are spoken depending on a person's mood, and a group of words that are specially called to livestock and domestic animals. Odagai category in the Kazakh language is a word class that differs from other word classes in terms of phonetics, grammar and semantics, and is also rich in emotional phenomena and intonation
Keywords: semantics; emotional; intonation; group